Analisis Faktor Kesiapan Digital Dalam Melakukan Adopsi Digital Pada Umkm: - - Luh Citra Resmi Cahyadi; Eka Putri Suryantari; Anak Agung Gede Krisna Murti (Jurnal Akuntansi Profesi, 2023)
Digital transformation presents new challenges for MSME players, where it requires readiness from MSME players to change the business system from conventional to digital. On the other hand, MSME players still have various obstacles such as lack of resources, low understanding and knowledge about digitalization, and lack of expertise regarding digitalization. This research was conducted on MSMEs in Denpasar City using data from 120 respondents. Samples were obtained using simple random sampling. A factor analysis performed on 11 variables obtained results, consisting of three factors that summarized the 11 variables analyzed. Factor 1 summarizes the variables Technology, Environment, Management, Organization, Knowledge, HR and Finance. Factor 2 summarizes the variables of Resources, Strategy and Regulation.Factor 3 summarizes infrastructure variables Keywords: Digitization, Digital Readiness, SMES